Penerapan Metode Naïve Bayes pada Sistem Seleksi Penerima Bantuan Bedah Rumah - Prastianti, Erlinda Nofa; Santi, Nirma Ceisa (Multidisciplinary Applications of Quantum Information Science (Al-Mantiq), 2023)
Home renovation is a succor given by the government for poor people to relieve their economics burden. Of CV Garuda Metta Consultant have team work there are with Dinas Cipta Karya and Dinas Bina Marga In Tambakrejo, Bojonegoro City, there is succor that coming from the region and the institution itself. The succor can be obtained if the candidates are suitable with the requirements and the criteria, such as land floor, bamboo wall, and unsafe roof condition. In addition, the criteria also specified on family income, land area of the house, and number of families. To select the candidates who get a chance of house renovation. This study will make a decision support system to help the get of home renovation receivers by the government in Sambirejo that using Naïve Bayes method. The purpose of this research is to provide suggestion for the priority of receivers of home renovation and to help the selectors in order that the receivers of home renovation in the Tambakrejo, Bojonegoro City in line with the target. This result of this research is a decision support system for the determination of the home renovation recipients based on defined criteria.